A numerical simulation of wheel spray for simplified vehicle model based on discrete phase method. (27th July 2015) - Hu, Xingjun; Liao, Lei; Lei, Yulong; Yang, Hanbo; Fan, Qingyin; Yang, Bo; Chang, Jing; Wang, Jingyu
Road spray greatly affects vehicle body soiling and driving safety. The study of road spray has attracted increasing attention. In this article, computational fluid dynamics software with widely used finite volume method code was employed to investigate the numerical simulation of spray induced by a simplified wheel model and a modified square-back model proposed by the Motor Industry Research Association. Shear stress transport k-omega turbulence model, discrete phase model, and Eulerian wall-film model were selected. In the simulation process, the phenomenon of breakup and coalescence of drops were considered, and the continuous and discrete phases were treated as two-way coupled in momentum and turbulent motion. The relationship between the vehicle external flow structure and body soiling was also discussed.